Phytochemical constituents and biological activities of longan (Dimocarpus longan Lour.) fruit: a review - Xiaofang Zhang; Sen Guo; Chi-Tang Ho; Naisheng Bai (Food Science and Human Wellness)
Longan (Dimocarpus longan Lour.), as an edible fruit and traditional Chinese medicine, has been consumed for thousands of years. Longan pulp has abundant nutritional phytochemicals such as protein, carbohydrate, vitamin C, polysaccharides, polyphenols, which shows multiple biological activities including antioxidant, immunomodulatory and antitumor effects. Longan pericarp also demonstrates biological activities because of its rich content of polysaccharides and polyphenols. This review summarizes the bioactive compounds and bioactivities of longan pulp and aims to provide comprehensive information for future development of longan as a functional health food.